Modelling of the multiaxial elasto-plastic behaviour of porous metals with internal gas pressure - Öchsner, Andreas (Elsevier BV, 2009)
The gas pressure built up within closed cells of porous or cellular metals influences the macroscopic behaviour during deformation. Another important process affected by internal pore pressure is the roll forming of structurally porous metals. During pressing and thermo-mechanical forming, the internal pressure of the pores and the temperature can rise to high levels. In this paper, the influence of the internal gas pressure on the mechanical behaviour of porous metals under different loading conditions is numerically investigated by the finite element method. It has been found that the internal gas pressure significantly influences the initial yielding as well as the macroscopic behaviour if the pressure is clearly less than a half of the yield strength of the base material. This can be found in scientific literature as a limit for a significant influence.